Region of interest-based tamper detection and lossless recovery watermarking scheme on MRI and X-ray medical images - Ooi, Jessie; Khor, Hui-Liang; Liew, Siau-Chuin (Institute of Physics Publishing, 2020)
The advancement of the technology has introduced many applications that will ease human daily process and improve the way people connect to each other. One of the applications that has been introduced to the user and vastly improve our life is the healthcare system. Health care system allows the medical practitioner to aware of the patient's previous health condition and documents their current. It also allows the medical practitioner to communicate with each other or get some advice from their peers and colleague even if they are far from each other physically. To ensure the authenticity of an image when it is transfer through the health care system, watermarking has been implemented. Through the process of watermarking the images, the authenticity of the images can be ensured. In this study, a ROI-based tamper detection and recovery watermarking scheme has been introduced. The proposed scheme has been tested out on the MRI and XA images. The PSNR value for MRI is 49.09 for the sequential mode and 49.07 in parallel mode. On the other hand, PSNR for XA images is 52.68 in the sequential mode and 52.68 in the parallel mode.